Association between P3 event‐related potential amplitude and externalizing disorders: A time‐domain and time‐frequency investigation of 29‐year‐old adults. (25th April 2013) - Yoon, Henry H.; Malone, Stephen M.; Burwell, Scott J.; Bernat, Edward M.; Iacono, William G.
Abstract This study determined whether time‐domain P3 amplitude and time‐frequency principal component (TF‐PC) reductions are present in adulthood (age 29) when participants have largely passed through the age of heaviest substance misuse. Participants were assessed from age 17 through 29 for lifetime externalizing (EXT) disorders. EEG comparisons from three topographic regions were examined for P3 amplitude and TF‐PCs at delta and theta frequency ranges. Significant P3 amplitude reductions were found in those with EXT for both regional and site‐Pz analyses, with stronger effects observed the greater the EXT comorbidity. Reductions were also observed in all eight TF‐PCs extracted, with a delta component yielding frontal effects not apparent in the time domain. Overall, results suggest that these brain measures continue, at age 29, to provide effective indices of EXT that potentially tap a neural substrate related to behavioral disinhibition.